A WoW player's guide to Aion. - Augustine, Josh.
Thinking of making the jump to Aion but nervous about starting over in a strange, new world? Don't worry--Josh Augustine explains Aion's beginning levels in terms every WoW player can understand.
Keywords: Computer games; PC gaming; War of the Worlds (WoW).; Aion